Pathological lesions in the immune organs of ducklings following experimental infection with goose parvovirus. (August 2019) - Liu, Hongmei; Yang, Chengcheng; Liu, Miaomiao; Ma, Kui; Huang, Xueting; Zhao, Yu; Hu, Dongmei; Qi, Kezong
Abstract: Goose parvovirus (GPV) is the etiological agent of Derzsy's disease, with a natural reservoir consisting only of geese and Muscovy ducks. However, the pathological changes in the immune organs of ducklings experimentally infected with GPV remain unknown. In this study, 2-day-old Cherry Valley ducklings were intramuscularly injected with GPV. Immune organs (e.g., thymus, bursa of Fabricius, spleen, Harderian gland, cecal tonsil, bone marrow, and peripheral blood lymphocytes [PBLs]) were collected 1, 3, 5, 7, 10, and 14 days post-infection (dpi). Pathological lesions were assessed by histology and the viral load was concurrently assessed using quantitative real-time polymerase chain reaction. GPV antigen was detected via immunofluorescence staining and immunohistochemistry. No clinical symptoms or death were observed in the infected ducklings from 1 to 14 dpi; however, lesions with different degrees of hemorrhage and hyperemia were observed in the thymus, spleen and Harderian gland. Lymphocyte necrosis was identified in the thymus and spleen. In the immune organs, the highest viral loads were found in the spleen at 7 dpi, followed by the bone marrow, PBLs, and cecal tonsil at 3 dpi, and the bursa, Harderian gland, and thymus at 1 dpi. GPV antigen was primarily expressed in the cecal tonsil, spleen, and Harderian gland at 5 dpi, as well as in the PBLs and bone marrow at 3 dpi. Our findings indicate widespread GPV replication and dissemination in the immune organs of Cherry Valley ducklings. Highlights: Pathological lesions in the immune organs of ducklings infected with GPV are shown for the first time in this study. The replication and dissemination of GPVs was widespread in immune organs of ducklings. GPVs are also pathogenic in ducklings.